Coding Landmarks: A Programming Approach to Spatial Thinking: Programming as a Scaffold for Spatial Reasoning (Constructionism Conference Proceedings, 2025)
While previous research has identified a correlation between spatial thinking and programming, little attention has been given to how programming can explicitly support students’ spatial reasoning during learning activities. This study explores the role of programming as a scaffold in supporting spatial reasoning and conceptualization among primary students while they navigate the digitally simulated space within a programming microworld. Using a design-based research approach, we analyze how programming activity guided students’ wayfinding in the digitally simulated space and supported the development of spatial concepts, providing them with the means to deploy computational thinking practices, like debugging, problem decomposition and abstraction to spatial problem solving.